Percepção de risco sanitário na bovinocultura de corte no estado de São Paulo - Caselani, Kelly [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The farming practices adopted by farmers are directly related to food safety, with repercussions on animal health, public health and in the environment. This study aimed to conduct a situation analysis on the sanitary risk perception of 90 farmers and/or rural administrators of beef cattle from 66 towns in the state of São Paulo in the use of food, agricultural inputs and for animal health. The interview answers were subjected to descriptive and multivariate statistics for multiple correspondence analysis, covering the following thematic areas: water, food, agricultural products and veterinary products. The results show a reasonable level of schooling among respondents, in the majority had more than 20 years in the activity and between 100 and 500 animals on their properties. Practices considered at risk were observed, as well as associations between socioeconomic factors and the sanitary risk perception, revealing similar behavior for different practices. Farmers with average schooling and livestock below 100 animals tend to believe that the water does not transmit disease to animals. Respondents with less than 10 years in activity and with less than 100 animals tend not to use feed/additives record in MAPA. Already respondents with herds between 100 and 500 animals, which formulate rations on production systems and employ byproduct of the industry in the feeding have a tendency to hire technical managers. A weak association between the absence of prescription of treatment by a veterinarian, lack of staff training, respondents with average schooling and time in less than 10 years activity was also detected. With the information generated, it can be concluded that the farmers and/or rural administrators need to implement changes in their farming practices in order to meet the demands of the market and increasingly demanding consumers. On the other hand, the results identify and nominate opportunities for public policies and services ...

As práticas pecuárias adotadas pelos produtores rurais têm relação direta com a segurança alimentar, com reflexos na saúde animal, na saúde pública e no ambiente. O presente estudo teve como objetivo realizar um diagnóstico de situação sobre a percepção de risco sanitário de 90 produtores e/ou administradores rurais da bovinocultura de corte de 66 municípios do Estado de São Paulo no uso de insumos alimentares, agrícolas e para a saúde animal. As respostas da entrevista foram submetidas à estatística descritiva e multivariada pela análise de correspondência múltipla, contemplando as seguintes áreas temáticas: água, alimentos, produtos agrícolas e produtos veterinários. Os resultados evidenciaram um nível razoável de escolaridade entre os respondentes, em que a maioria estava há mais de 20 anos na atividade e possuía entre 100 e 500 animais em suas propriedades. Práticas consideradas de risco foram observadas, além de associações entre fatores socioeconômicos e de percepção de risco sanitário, revelando comportamentos semelhantes para diferentes práticas. Produtores rurais com escolaridade média e com rebanhos inferiores a 100 animais tendem a acreditar que a água não transmite doença aos animais. Respondentes com menos de 10 anos na atividade e com menos de 100 animais tendem a não utilizar rações/aditivos com registro no MAPA. Já os entrevistados com rebanhos entre 100 e 500 animais, que formulam ração nos sistemas de produção e empregam subproduto da indústria na alimentação, têm uma tendência a contratar responsáveis técnicos. Uma discreta associação entre a ausência de prescrição de tratamento por médico veterinário, ausência de treinamento dos funcionários, respondentes com escolaridade média e com tempo na atividade inferior a 10 anos também foi detectada. Com as informações geradas, é possível concluir que os produtores e/ou administradores rurais necessitam ...
Keywords: Bovino - Criação; Bovino de corte; Análise de correspondência (Estatística); Fatores socioeconômicos; Saúde pública; Public health